(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
The research presented in the paper is directed to creating possibilities for production of multilayered plywood that are resistant to prolonged water impact, as well as to mutual impact of water and heat. The aim of the conducted research consists of the possibility for production of stable multifunctional plywood made from coniferous raw material. For that purpose experimental multilayered plywood panels are made from peeled black pine veneers bonded with water-soluble phenol formaldehyde resin. The experimental panels were subjected to standard laboratory tests in conditions of water regimes in order to define the water resistance and dimensional stability under water impact and mutual impact of water and heat, as well as to determine the degree of adhesion between the veneers. The research showed that panels were characterized by high stability during this kind of treatment. The panels showed consistency in form and dimensions, as well as consistency of the adhesion in glue lines.